LibID, should my library have? - Rzeczkowski, Wiktor (My University, 2015)
LibID is an authorization-based service model for control of access to library online resources. LibID can help libraries to address access control problems, provide better service and achieve better service recognition.
This is a minimally edited 36x60 inch poster presented on September 10, 2015 at Access Conference 2015, Toronto (the PDF source is 18x30 inch).
Keywords: LibID; access control; electronic resources; authorization; authentication; LDAP; libraries; personalized services; service recognition